2011
DOI: 10.1002/bjs.7460
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of intraoperative versus preoperative endoscopic sphincterotomy in patients with gallbladder and suspected common bile duct stones

Abstract: In patients with gallbladder and common bile duct stones, IOES is as effective and safe as POES and results in a significantly shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 52 publications
0
41
1
4
Order By: Relevance
“…A meta-analysis of randomized trials confirmed that IOES during LC is as effective and safe as postoperative therapeutic ERCP and results in significantly shorter hospital stay [43]. Intraoperative ERCP during LC has many theoretical benefits.…”
Section: Percutaneous Tube Drainage Followed By Ercp and Stenting Wasmentioning
confidence: 88%
“…A meta-analysis of randomized trials confirmed that IOES during LC is as effective and safe as postoperative therapeutic ERCP and results in significantly shorter hospital stay [43]. Intraoperative ERCP during LC has many theoretical benefits.…”
Section: Percutaneous Tube Drainage Followed By Ercp and Stenting Wasmentioning
confidence: 88%
“…A meta-analysis of four RCTs involving 532 patients comparing preoperative EST and intraoperative EST using the rendezvous technique reported that post-EST complications occurred at a significantly lower rate and hospital stays were significantly shorter with intraoperative EST. There was no difference in the stone removal rate [127]. Although the intraoperative rendezvous technique facilitates bile duct cannulation and is expected to reduce the incidence of pancreatitis and other complications, it can be performed only at resource-rich institutions because it requires prolonged surgery time and an endoscopic specialist to be available in the operating room.…”
Section: Commentarymentioning
confidence: 98%
“…The surgical procedures in this meta-analysis included open (seven trials) and laparoscopic (five trials) procedures, and the subanalysis also did not reveal any differences. When cholecystectomy was performed at the same time as the treatment for choledocholithiasis, the hospital stay was reduced compared with two-stage treatment despite there being no difference in the stone removal rate [126,127]. However, a prospective national survey conducted by the Japan Biliary Association Scientific Committee [128] (literature published outside the search period) reported that only 3 of 77 cases of choledocholithiasis were treated surgically (3.9%), one with laparoscopic surgery and two with open choledochotomy.…”
Section: Commentarymentioning
confidence: 99%
“…This advantage has been highlighted by surgeons who are also trained to perform endoscopic clearance [17]. In a meta-analysis, Gurusamy et al reported intraoperative CBD clearance to be as safe and effective as preoperative clearance with an added advantage of shorter hospital stay [18].…”
Section: Discussionmentioning
confidence: 99%